Alternative corporate governance systems in Japanese firms: Implications for a shift to stockholder-centered corporate governance - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2001)
In Asia, the recent catastrophic decline in regional stock markets, continuing currency crisis and failures of major financial institutions and industrial corporations have increased domestic and international interest in corporate governance. Nowhere is this greater than in Japan where financial institution reform has catapulted this to the fore. Agency theory and institutional theory, together with comparative case examples, are used in a study to derive some propositions on the dynamics of changing corporate governance systems in Japanese firms. The study argues for the co-existence of stakeholder and shareholder-centered corporate governance systems in Japan. This argument has an important implication for corporate governance research and agency theory. Namely, changes in ownership structure and institutional expectations would force firms to focus on maximizing shareholder value even where the interests of stakeholders are more emphasized. It suggests an environmental selection mechanism to ensure the emergence of appropriate corporate governance mechanisms to solve the agency problem. Further, the loss of competitiveness and the prolonged poor performance of firms can change the institutional norms to emphasize asset efficiency and transparency rather than stability and business ties.